2019
DOI: 10.1152/japplphysiol.00753.2018
|View full text |Cite
|
Sign up to set email alerts
|

Spleen reactivity during incremental ascent to altitude

Abstract: The spleen contains a reservoir of red blood cells that are mobilized into circulation when under physiological stress. Despite the spleen having an established role in compensation to acute hypoxia, no previous work has assessed the role of the spleen during ascent to high altitude. Twelve participants completed 2 min of handgrip exercise at 30% of maximal voluntary contraction at 1,045, 3,440, and 4,240 m. In a subset of eight participants, an infusion of phenylephrine hydrochloride was administered at a dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 44 publications
(68 reference statements)
0
22
3
Order By: Relevance
“…In contrast, a recent investigation found that spleen size was unchanged throughout incremental ascent at HA, while injection of phenylephrine hydrochloride induced spleen contraction during ascent, but not hand grip exercise (Purdy et al., 2018). The authors concluded that the spleen does not contribute to the acclimatization process at HA.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, a recent investigation found that spleen size was unchanged throughout incremental ascent at HA, while injection of phenylephrine hydrochloride induced spleen contraction during ascent, but not hand grip exercise (Purdy et al., 2018). The authors concluded that the spleen does not contribute to the acclimatization process at HA.…”
Section: Discussionmentioning
confidence: 90%
“…The spleen is mainly innervated by sympathetic nerves with both α-and β-adrenoceptors (Ayers et al 1972) and spleen contraction can probably be induced by both neural input and catecholamine release (Stewart and McKenzie 2002). While resting spleen volumes observed by Purdy et al (2018) at 1045 m (273 mL), were similar to what we observed at 1370 m (252 mL), their handgrip exercise at 1045 m only caused a spleen contraction of 8%, while in our study, the step test caused a 21% spleen contraction. Likewise, the Hct in their study increased from baseline by 4%, while in our study, by 6%.…”
Section: Discussionmentioning
confidence: 99%
“…There could also be other vascular responses from injection of the phenylephrine bolus, e.g., overstimulation of the baroreceptors, which could have blunted the endogenous sympathetic activity. Therefore, we consider the study by Purdy et al (2018) inconclusive of whether spleen contraction occurs during exercise at high altitude. Their lack of effect of altitude on resting spleen volume remains contrasting to our observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While hypoxia is identified as the main stimulus initiating spleen contraction, hypercapnia has a contributing role (Richardson et al, 2012). Spleen contraction is also initiated by intense exercise (Sandler et al, 1984;Laub et al, 1993) and is likely also initiated by general sympathetic activation (Frances et al, 2008;Purdy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%